PENGARUH REGULASI DIRI TERHADAP PROKRASTINASI AKADEMIK PADA SISWA SMA - Dwi Kencana Wulan, Putri Ramadhani Ayu Ardina (Perspektif Ilmu Pendidikan, 2016)
Academic procrastination is one of the problems student usually faced, caused by fatigue or boredom. While in the other side, students needs the ability to regulate themselves for striving their goals. This study aims to determine the influence of self-regulation towards academic procrastination using quantitative method with psychological scale in questionnaire form. This research instrument was developed based on the theory of academic procrastination by Ferrari and self-regulation theory by Barkley. This research was conducted in June 2016. The samples of this study were the tenth grade students of SMA Negeri 10 Jakarta (State Senior High School of Jakarta). The sampling technic used was cluster random sampling. The analytical statistic used to test the hypothesis was regression analysis using SPSS program verse 19 and Rasch Model. The Result of this study indicates that there is negative effect of self-regulation towards academic procrastination. It shows that the higher self-regulation performed, then the lower academic procrastination will become. The influence which resulted by self-regulation towards academic procrastination is 29,3% and the rest 70,7%, is caused by another factor.